2023
DOI: 10.1038/s41467-023-38974-9
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional mapping of dynamic longitudinal brain subcortical development and early learning functions in infants

Abstract: Brain subcortical structures are paramount in many cognitive functions and their aberrations during infancy are predisposed to various neurodevelopmental and neuropsychiatric disorders, making it highly essential to characterize the early subcortical normative growth patterns. This study investigates the volumetric development and surface area expansion of six subcortical structures and their associations with Mullen scales of early learning by leveraging 513 high-resolution longitudinal MRI scans within the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Our ability to probe individual cognitive subscales provided results that also align with previous findings and provide insight to potential gut-microbial connections between cognition and neuroanatomy. For example, a longitudinal neurocognitive development study pointed at bilateral associations between the thalamus and the expressive language component of the Mullen scales ( 61 ). In line with this finding, we found that taxa such as B. wexlerae and A. hadrus were among the top 15% important predictors on both left and right thalamus and the expressive language subscale.…”
Section: Discussionmentioning
confidence: 99%
“…Our ability to probe individual cognitive subscales provided results that also align with previous findings and provide insight to potential gut-microbial connections between cognition and neuroanatomy. For example, a longitudinal neurocognitive development study pointed at bilateral associations between the thalamus and the expressive language component of the Mullen scales ( 61 ). In line with this finding, we found that taxa such as B. wexlerae and A. hadrus were among the top 15% important predictors on both left and right thalamus and the expressive language subscale.…”
Section: Discussionmentioning
confidence: 99%